2015
DOI: 10.1111/ajt.13060
|View full text |Cite
|
Sign up to set email alerts
|

Compared Efficacy of Preservation Solutions in Liver Transplantation: A Long-Term Graft Outcome Study From the European Liver Transplant Registry

Abstract: Between 2003 and 2012, 42 869 first liver transplantations performed in Europe with the use of either University of Wisconsin solution (UW; N = 24 562), histidine-tryptophan-ketoglutarate(HTK; N = 8696), Celsior solution (CE; N = 7756) or Institute Georges Lopez preservation solution (IGL-1; N = 1855) preserved grafts. Alternative solutions to the UW were increasingly used during the last decade. Overall, 3-year graft survival was higher with UW, IGL-1 and CE (75%, 75% and 73%, respectively), compared to the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
135
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 23 publications
5
135
0
3
Order By: Relevance
“…The overall 3-year graft survival was higher with UW, IGL-1 and CE (75%, 75% and 73%, respectively), compared to HTK (69%) (P < 0.0001) [67] . The same trend was observed with a total ischemia time > 12 h or for grafts injury and several mechanisms have been proposed to explain this.…”
Section: Preservation Solutionsmentioning
confidence: 88%
See 2 more Smart Citations
“…The overall 3-year graft survival was higher with UW, IGL-1 and CE (75%, 75% and 73%, respectively), compared to HTK (69%) (P < 0.0001) [67] . The same trend was observed with a total ischemia time > 12 h or for grafts injury and several mechanisms have been proposed to explain this.…”
Section: Preservation Solutionsmentioning
confidence: 88%
“…Viscous preservation solutions may negatively impact on efficacy of flushing of the bile ducts capillaries, resulting in residual bile crystallization and obstruction [111][112][113] . Use of less viscous solutions, like HTK, seems to provide better results in reducing the incidence of biliary tract injuries, despite the recent results of the European liver transplant registry data [67,112] . In a large study, a CIT > 10 h was found to be associated with a higher incidence of ITBL and every effort should be made not to exceed this limit [113] .…”
Section: Itblmentioning
confidence: 98%
See 1 more Smart Citation
“…IGL1 exhibits similar positive outcomes as UW (Codas et al 2009) or even better (Badet et al 2005). Donderó et al (2010) and Adam et al (2015), in a liver transplantation review, summarized the data related to the utility of UW solution and IGL1 solution to resist graft rejection. A slight graft rejection increase with CE solution and a significant reduction with HTK solution was observed.…”
Section: Preservation Solutionsmentioning
confidence: 99%
“…Viscosity data refer to a temperature of 4°C. From Petrowsky and Clavien (2014) and Adam et al (2015). to IRI, partly due to protein kinase B (PKB) and eNOS signaling activation, and reduced cytokine release (Zaouali et al 2010a,b).…”
Section: Preservation Solutionsmentioning
confidence: 99%